Extensive communication and the format of the online scientific journal - Simeão, Elmira (2004)
The scientific journal has been greatly affected by the advent of its online digital accessibility. It is the priority publication medium for scientific communication, one of the document categories where changes in the electronic format uncover an extensive action, different from traditional practices. The extensive communication — a.k.a. the emblematic model of network interactions — comes as much in new forms of document production, as well as in the organization of the technical landscape in which scientific information adapts to flexible and unstable forms. Gradual changes (in support, format, content, and publication type) were observed in 400 online electronic journals, being all by main international publishers, as made available at CAPES portal (www.periodicos.capes.gov.br). The portal offers access to the complete text of a lot of publication, encyclopedias, databases, etc., supplied by editors and international distributors. In all the platforms we can find specific search tools that make possible bibliographical searches, alert services and other products and services, as well as information of technical and scientific interest. A data collection was assembled through a checklist for 70 variables, and the results were inserted in a spreadsheet for an initial analysis. Afterwards, data were cross-examined through the use of the SPSS software for statistical analysis. This investigation has shown that the new format stands out through the insertion of tools and services, strengthening extensive communication by means of interactivity, hypertextuality, and hypermediation, a. k. a., the main distinctive features of the electronic format. After technological resources mature the online format, they establish a new perception of the journal contents. The variables were grouped according to their pertinence to the studied aspects in the electronic format, and were expressed in percentage ratios. The results display the dependence of the electronic on the printed format. By combining all the variables once again to measure the levels of interactivity, hypertextuality, and hypermediation, journals were grouped by platform (i. e., the online publishing base as, for example, Scielo, Science Direct, Gale, OVID, etc.) to test for interactivity, hypertextuality, and hypermediation levels among platforms. The descriptive measures of indexes were first calculated: average, standard deviation, minimum value, maximum value, percentage ratios — among other data — to confirm level variations of each one of the characteristics among the platforms. Observing the grouping by platform, the results have shown evidence that a direct relationship (in other words, the most interactive groups are not necessarily the most hypertextual or hypermediatic ones) does not exist among the three characteristic features of the online electronic format. The online journal is using a communication in a differentiated dimension from the traditional system. The performance of the journals was also evaluated comparatively among platforms. At this stage in the evolution of electronic publishing, serious experimentation is needed. Models like CAPES Portal should be developed, allowing for continued expansion and enhancement of scholarly communication.